Emodin Protects Against Lipopolysaccharide-Induced Acute Lung Injury via the JNK/Nur77/c-Jun Signaling Pathway - Xie, Pei; Yan, Li-Jun; Zhou, Hong-Ling; Cao, Hui-Hui; Zheng, Yuan-Ru; Lu, Zi-Bin; Yang, Hua-Yi; Ma, Jia-Mei; Chen, Yu-Yao; Huo, Chuying; Tian, Chunyang; Liu, Jun-Shan; et al. (Frontiers in Pharmacology, 2022)
Background: Acute lung injury (ALI) is a serious inflammatory disease with clinical manifestations of hypoxemia and respiratory failure. Presently, there is no effective treatment of ALI. Although emodin from Rheum palmatum L. exerts anti-ALI properties, the underlying mechanisms have not been fully explored. Purpose: This study aimed to investigate the therapeutic effect and mechanism of emodin on LPS-induced ALI in mice. Methods: RAW264.7 cells and zebrafish larvae were stimulated by LPS to establish inflammatory models. The anti-inflammatory effect of emodin was assessed by ELISA, flow cytometric analysis, and survival analysis. In vitro mechanisms were explored by using Western blotting, luciferase assay, electrophoretic mobility shift assay (EMSA), and small interfering RNA (siRNA) approach. The acute lung injury model in mice was established by the intratracheal administration of LPS, and the underlying mechanisms were assessed by detecting changes in histopathological and inflammatory markers and Western blotting in lung tissues. Results: Emodin inhibited the inflammatory factor production and oxidative stress in RAW264.7 cells, and prolonged the survival of zebrafish larvae after LPS stimulation. Emodin suppressed the expression levels of phosphorylated JNK at Thr183/tyr182 and phosphorylated Nur77 at Ser351 and c-Jun, and increased the expression level of Nur77 in LPS-stimulated RAW264.7 cells, while these regulatory effects of emodin on Nur77/c-Jun were counteracted by JNK activators. The overexpression of JNK dampened the emodin-mediated increase in Nur77 luciferase activity and Nur77 expression. Moreover, the inhibitory effect of emodin on c-Jun can be attenuated by Nur77 siRNA. Furthermore, emodin alleviated LPS-induced ALI in mice through the regulation of the JNK/Nur77/c-Jun pathway. Conclusions: Emodin protects against LPS-induced ALI through regulation on JNK/Nur77/c-Jun signaling. Our results indicate the potential of emodin in the treatment of ALI.